Hak-Hak Penyandang Disabilitas dalam Pemilu Indonesia: Tinjauan Kritis Kesenjangan Normatif-Praktis dalam Undang-Undang Nomor 7 Tahun 2017 - Orleta J. W. Helniha; Krisman Wilhelmus; M. Firman Mustika (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2026)
Law Number 7 of 2017 concerning General Elections is one of the crucial regulations in Indonesia’s electoral system. Article 5 of this law emphasizes the principles of equality and non-discrimination, including those related to the political rights of persons with disabilities. Although normatively regulated, Article 5 has not yet been effectively implemented, according to various reports. Given this reality, this study aims to examine the implementation of Article 5 of the Election Law regarding the fulfillment of political rights for persons with disabilities as a manifestation of social justice. This research employs a literature study method with a qualitative approach. The findings recommend several strategic measures for future election administration, namely: standardization of accessible polling stations (TPS) for persons with disabilities, development of a voter registration information system for persons with disabilities, capacity building for Voting Organizer Group (KPPS) officers, provision of special services at polling stations, and optimization of supervisory services by the Election Supervisory Agency (Bawaslu).